Olhos eletrônicos sobre o corpo pandêmico: uma poética da criação em dança sob filmagem - RODRIGUES, Airleise Sarges (2022)
This study deals with a theoretical-practical research on the process of creation in videodance in which I, as an artist of the scene, seek, based on the pandemic theme, to analyze my own body in the midst of a sanitary crisis, while at the same time developing a videodance that aims to show a hybrid body influenced by pandemics, in addition to trying to answer the guiding question of how the creative process in dance is configured when I put myself in front of the camera. Thus, I tried to dialogue in the light of theories of videodance, the body and the creative process of renowned theorists such as Lobo and Navas (2008), Ostrower (2008), Merleau-Ponty (1999) and others. This experience made me realize the plasticity of the creative process and the bodily sensations that constantly dialogue with the footage, inaugurating a new body, a new dance. I hope to contribute to the Physical Education community through the understanding of corporeality and its relationship with technology, in this case, the cell phone camera.